Abundancia y diversidad en un bosque de terraza baja inundable por agua negra, distrito de Lagunas, Loreto. Perú, 2024 - Armas Lanaro, Segundo Antonio (2025)
The study was conducted in a low terrace forest flooded by sewage in the native community of Huancayo – Nucuray River, Lagunas district, Alto Amazonas province, Loreto department. Forest tree species with dbh >= 30 cm were evaluated in 26 sampling units of half a hectare. A total of 779 trees, 25 forest species, 23 genera, and 12 botanical families were recorded. The most abundant families were Fabaceae (28.5%), Malvaceae (18.1%), and Myristicaceae (17.1%). The density was 33.87 trees/ha, calculated on a total of 779 trees in 26 units of 0.5 ha. Four dominant species accounted for more than 50% of the total IVI: Virola elongata, Copaifera reticulata, Ceiba samauma, and Myroxylon balsamum. The forest presented a medium-low diversity. (Shannon-Wiener (H'): 2.29; Simpson (1 D): 0.888; and Margalef: 1.9). It is recommended to develop sustainable forest management plans focused on Virola elongata, Copaifera reticulata, Ceiba samauma, and Myroxylon balsamum, respecting cutting and regeneration cycles.